The Canadian yearbook of international law, 2006 = Annuaire canadien de droit international, 2006. - McRae, Don M. (Canadian yearbook of international law, 2007)
This is the forty-fourth volume of The Canadian Yearbook of International Law, the first volume of which was published in 1963. The Yearbook is issued annually under the auspices of the Canadian Branch of the International Law Association (Canadian Society of International Law) and the Canadian Council on International Law. The Editor-in-Chief is D.M. McRae, Faculty of Law, University of Ottawa, and the Associate Editor is A.L.C. de Mestral, Faculty of Law, McGill University. Its Boards of Editors includes scholars from leading universities in Canada. The Yearbook contains articles of lasting.